(3cJGH aj GdRQGYI heG jJYdb HgG hCSeGA GdCTLGQ hZjQ Pdcs ((3eMeO Hf GSeGYjd GdNGHMi GdeUQj GdMfaj s)
(3ChdgG (B:s
(3hHYO agPG Gdaf GdQGHY ef Gdafhf GdJi OGaY GdYbd ai bOQJgG gh GdfaS s
(3BNQgG (B:s
(3hdh SdcJ GjgG GdfQLS CYOd efgL deG aCLRJ CNGc GdHfaSL Ke ChUi cdG efge HUGMHg HYO Cf CWfH ai hUa efGbHghgPG BNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B191 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdRQGYI h GdCYTGHs